Infeksi saluran kemih berhubungan dengan peningkatan nilai prostate specific antigen pada pasien benign prostate hyperplasia di Rumah Sakit Sanglah - Nyoman Khrisna Dharmawan; Gede Wirya Kusuma Duarsa (Universitas Udayana, 2018)
Increasing the value of Prostate Specific Antigen (PSA) is caused by various things related to abnormal enlargement of the prostate such as prostate cancer and benign prostate hyperplasia (BPH), urinary tract infection (UTI) can cause inflammation and irritation of the epithelial cells of the prostate that can cause swelling of the prostate. This study aims to determine whether UTI associated with increased PSA value in patients with BPH. This research was conducted by recording a patient who came to the urology clinic with a diagnosis of BPH between July and October 2015, then patients were evaluated with a urine sample taken for further cultured to determine if the patient has a UTI or not. Then also taken blood samples to determine levels of PSA values ??with a cut-off point of 4 ng / ml. The statistical analysis used is the test Shapiro Wilk normality test, and Chi-Square to determine the correlation between PSA and UTI. Obtained 24 BPH patients were divided into 2 groups: 12 patients with BPH with positive urine culture and 12 BPH patients with negative urine culture with a mean age of the sample in the study was 64 ± 2 years. The mean rank of PSA in BPH patient group with positive urine culture was 17.25, while in BPH patients with negative urine cultures of 7.75 (p = 0.001), In the test Chi Square correlation obtained 6 patients in this group of patients BPH with positive urine culture had a high PSA values ??and the rest have lower psa (p = 0.005). There can be concluded that the relationship between the PSA value by urine culture in patients with BPH Keywords: Benign Prostate Hyperplasia, Urinary Tract Infection, Prostate Specific Antigen